Supersymmetry in quantum mechanics - Cooper, Fred; Khare, Avinash; Sukhatme, Uday (Singapore: World Scientific, 2001)
This text has been written to be accessible to students in advanced undergraduate quantum mechanics courses. Problems have been given at the end of each chapter, along with complete solutions to all the problems. The book also includes material of interest in current research.
Includes bibliographical references; Appendix A-D, 157-206p.; Index 207-210p.
Keywords: Quantum mechanics; Supersymmetry; Physics